"The Booklet Helped Me Not to Panic": A Pilot of a Decision Aid for Asymptomatic Women With Ovarian Cancer and With Rising CA-125 Levels. Issue 4 (1st April 2011) - Anderson, Caroline; Carter, Jonathan; Nattress, Kathryn; Beale, Philip; Philp, Shannon; Harrison, James; Juraskova, Ilona
Abstract : Introduction: After first-line treatment, cancer antigen 125 (CA-125) levels can rise many months before there are other signs of recurrent ovarian cancer, leading to a difficult choice about when to initiate second-line treatment. To assist with shared decision making, a decision aid (DA) booklet that compared the options of "wait and see, " chemotherapy, and tamoxifen was developed and piloted. Methods: Twenty patients attending clinics at 2 cancer centers agreed to read the DA booklet, complete a set of standardized and purpose-designed measures, and provide feedback on the DA booklet via a semistructured telephone interview. Participants were either currently making the decision about treatment (n = 14) or had progressed and were now receiving treatment of recurrent cancer (n = 6). Results: Most patients found information in the DA easy to understand (79%) and presented in a balanced way (90%), and almost all (95%) would recommend the booklet to others facing a similar decision. Women showed a good understanding of information contained in the booklet, with a mean of 88% answering each of the knowledge questions correctly. Compared with other ovarian cancer studies, decisional conflict scores were lower, whereas anxiety scores were high but similar to 1 comparable study. Suggestions for improvement related to information about recurrent ovarian cancer and the decision making worksheets. Conclusions: The DA seems an acceptable and useful decision making resource in this setting. Strategies for reducing anxiety levels linked to booklet administration are outlined. The DA has been revised to reflect pilot findings and changes in clinical evidence, and the effectiveness of the DA in reducing decisional conflict and regret is being evaluated in a randomized controlled trial.